Incorporating Resilience to Platforms based on Edge and Fog Computing - Medina, Santiago (2022)
In recent years, Internet of Things (IoT) has become extremely popular because of its ability of sensing information from the environment and processing it in the cloud. Edge and Fog Computing are new paradigms that aim to localize some of the processing near the sensors, helping to cope with high communications latencies and bandwidth bottlenecks. As Wireless Sensor Networks (WSN) and Fog nodes are prone to failure, affecting system reliability and performance, the implementation of resilience strategies becomes essential to ensure reliable delivery of data and system availability during interruptions or in the presence of faults. In this article, we present three lines of research in progress: Redundant Image Processing, Integration of a WSN with an IoT Platform for Intelligent Control and Resilient Monitorization and Control of Robots. We aim to incorporate resilience mechanisms to platforms that integrate Edge, Fog and Cloud Computing, and to evaluate the proposed solutions in terms of the coverage achieved, processing and communication times and power consumption.